Functional analysis of Pacific oyster (Crassostrea gigas) β-thymosin: Focus on antimicrobial activity. Issue 1 (July 2015) - Nam, Bo-Hye; Seo, Jung-Kil; Lee, Min Jeong; Kim, Young-Ok; Kim, Dong-Gyun; An, Cheul Min; Park, Nam Gyu
Abstract: An antimicrobial peptide, ∼5 kDa in size, was isolated and purified in its active form from the mantle of the Pacific oyster Crassostrea gigas by C18 reversed-phase high-performance liquid chromatography. Matrix-assisted laser desorption ionisation time-of-flight analysis revealed 4656.4 Da of the purified and unreduced peptide. A comparison of the N-terminal amino acid sequence of oyster antimicrobial peptide with deduced amino acid sequences in our local expressed sequence tag (EST) database of C. gigas (unpublished data) revealed that the oyster antimicrobial peptide sequence entirely matched the deduced amino acid sequence of an EST clone (HM-8_A04), which was highly homologous with the β-thymosin of other species. The cDNA possessed a 126-bp open reading frame that encoded a protein of 41 amino acids. To confirm the antimicrobial activity of C. gigas β-thymosin, we overexpressed a recombinant β-thymosin (rcgTβ) using a pET22 expression plasmid in an Escherichia coli system. The antimicrobial activity of rcgTβ was evaluated and demonstrated using a bacterial growth inhibition test in both liquid and solid cultures. Highlights: A β-thymosin homologous peptide was isolated from an acidified mantle extract of Pacific oyster, Crassostrea gigas . Antimicrobial activity of the β-thymosin homologous peptide was confirmed by recombinant protein production. This recombinant protein showed potent antimicrobial activity against Gram-positive and Gram-negative bacteria, and Candida albicans .